Perception and misperception in international politics - Jervis, Robert 1940- (Princeton, New Jersey Princeton University Press, 1976)
This study of perception and misperception in foreign policy was a landmark in the application of cognitive psychology to political decision making. The "New York Times" called it, in an article published nearly ten years after the book's appearance, "the seminal statement of principles underlying political psychology." The perspective established by Jervis remains an important counterpoint to structural explanations of international politics, and from it has developed a large literature on the psychology of leaders and the problems of decision making under conditions of incomplete information, stress, and cognitive bias. Jervis begins by describing the process of perception (for example, how decision makers learn from history) and then explores common forms of misperception (such as overestimating one's influence). Finally, he tests his ideas through a number of important events in international relations from nineteenth- and twentieth-century European history. In a contemporary application of Jervis's ideas, some argue that Saddam Hussein invaded Kuwait in 1990 in part because he misread the signals of American leaders with regard to the independence of Kuwait. Also, leaders of the United States and Iraq in the run-up to the most recent Gulf War might have been operating under cognitive biases that made them value certain kinds of information more than others, whether or not the information was true. Jervis proved that, once a leader believed something, that perception would influence the way the leader perceived all other relevant information.--Publisher description.
Perception and the level of analysis problem -- External stimuli, internal processes, and intentions -- Deterrence, the spiral model, and intentions of the adversary -- Cognitive consistency and the interaction between theory and data -- The impact of the evoked set -- How decision-makers learn from history -- Attitude change -- Perceptions of centralization -- Overestimating one's importance as influence or target -- The influence of desires and fears on perception -- Cognitive dissonance and international relations -- Minimizing misperception.
Includes bibliographical references (pages [425]-431) and index
Keywords: International relations -- Research